(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
The behavior of 5,5-disubstituted-3-(prop-2-ynyl)dihydrofuran-2(3H)-ones under conditions of Mannich and coupling reactions have been studied. It was established that their interaction with paraform and secondary amines in the presence of copper halogenides (I) afforded aminobutynyl derivatives of γ-lactones, and the coupling reactions with active halogenides resulted in butynalkynyl derivatives. Synthesized compounds are representatives of new systems earlier not described in the literature.